Lobular capillary hemangiomas: An epidemiologic report, with emphasis on cutaneous lesions - Harris, M.N.; Desai, R.; Chuang, T-Y; Hood, A.F.; Mirowski, G.W. (Journal of the American Academy of Dermatology, 2000)
Background: Lobular capillary hemangiomas (pyogenic granulomas) occur on both mucosal and cutaneous surfaces. There are conflicting data regarding the increased prevalence of lobular capillary hemangiomas in female versus male subjects. Some studies have noted a female predominance of lobular capillary hemangiomas, but other studies do not reveal such a disparity. Because of an increased prevalence during pregnancy, oral tumors are also known as “granuloma gravidarum” or “pregnancy tumors.” A hormonal influence for these mucosal lesions has been postulated. There are, however, no studies that address a possible relationship between hormones and cutaneous lesions. Objective: This study presents the epidemiology of lobular capillary hemangiomas, with an emphasis on cutaneous lesions. Methods: We reviewed 63,759 dermatopathology reports from a regional, private dermatopathology laboratory and found 325 cases of lobular capillary hemangiomas over a 1-year period. Results: In our study of lobular capillary hemangiomas, cutaneous lesions accounted for 86%, with mucosal lesions representing only 12% of cases. Seven cases were excluded (one was intravascular, two were subcutaneous, and in 4 the location was not specified). Overall, male patients outnumbered female patients. The peak incidence for cutaneous lobular capillary hemangiomas was found in the second decade of life. The most common cutaneous sites were the trunk, upper extremities, and head. Mucosal lesions were primarily seen on the lips, gingiva, and tongue, and these affected females more than males by a ratio of 2:1, most commonly in the fourth decade of life. Conclusion: Cutaneous lobular capillary hemangiomas were equally prevalent in male and female patients. This would refute a female hormonal influence in the induction of cutaneous lobular capillary hemangiomas. Our data may suggest a hormonal influence on mucosal lesions because mucosal lobular capillary hemangiomas were twice as common in female patients. However, the small number of lesions in our study precludes us from making such a conclusion. (J Am Acad Dermatol 2000;42:1012–6.)